Die kanoniese benadering van ChiIds: 'n Paradigmaskuif? - Claasen, C. F. (Verbum et ecclesia, 1997)
The canonical approach of Childs: A paradigm shift? It is said that the canonical approach by Childs represents a paradigm shift. Accordingly it is stated that Chi/ds operates a-historically. This article hypothesised that the canonical approach still finds itself in the mainstream of historical criticism. Chi/ds depends on the result of the historical critical method for the implementation of his approach. Chi/ds still finds himself in the same cadre as his mentors Karl Barth and Gerhard von Rad. He can therefore not be labelled as a-historical.